VALUASI EKONOMI TINGKAT KERUSAKAN BANGUNAN PERMUKIMAN AKIBAT BANJIR LAHAR DI KALI PUTIH KABUPATEN MAGELANG - Rosalina Kumalawati (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractThe purposes of this study are to identify the zonation of lahar-affected regions and thenumber of damaged houses due to lahar, as well as to make an economic valuation onsettlement building damage due to lahar in Kali Putih, Magelang Regency.The study was conducted by using a survey method based on physical and administrativezonations. The former was based on overflow width of lahar in Kali Putih after the Merapierruption in 2010, while the latter was based on subdistrict. Each of the zonation units wassampled. The sampling was carried out on the basis of settlement building vulnerability dueto lahar. The sample was represented by 59 respondents and three times of Focus GroupDiscussion (FGD) during the study.Results of the study show that, first, the overflow width of lahar in the location of study was1.785 km2. The widest overflow was in Sirahan Village, i.e. 0.813 km2 or 45.532 %, and thenarrowest one was in Blongkeng Village, Ngluwar Subdistrict, i.e. 0.001 km2 or 0.057%.Second, the number of houses affected by lahar was 1,290 houses. Settlement buildingdamage was dominantly due to collapse/washed away (814 houses), moderately damaged(200 houses), ligthly damaged (140 houses), severely damaged (71 houses), and relativelyundamaged (65 houses). A settlement mostly affected by the impact of lahar was SirahanVillage, Salam Subdistrict, i.e. 860 houses. Third, the largest lost resulted from the laharwas related to permanent houses, i.e. approximately IDR104,000,000.00 because theconstruction cost for the permanent houses was more expensive than that for semi-permanentand non-permanent ones.